THE USE OF CHROMATOGRAPHIC METHODS IN DETERMINING THE COMPOSITION OF SUBSTANCES IN SCHOOL CHEMISTRY LESSONS (Academia Science Repository, 2023)
This article covers the use of chromatographic methods for determining the composition of substances in school chemistry lessons and its science, scope, purpose and objectives.